Resistance from the Right Conservatives and the Campus Wars in Modern America. - Shepherd, Lauren Lassabe (Justice, Power, and Politics Series., 2023)
"This history offers a new look at conservatives and education in the United States. Pivoting from studies that emphasize the dominance of progressivism on American college campuses during the late sixties to early seventies, Shepherd positions conservative critiques of and agendas in American higher education as more than a passing phase in her history of campus wars in the late twentieth century. Shepherd explores the ways conservative students, enabled by wealthy CEOs and right-wing intellectuals, worked to counter liberal traditions, movements, and other dynamics in the American academy through themes of counter-messaging, appeals to authority, and punishment from 1967-1972"--